THE ART OF BLUNDERING. THE LITERARY TRAVELS OF KARL ČAPEK AND SÁNDOR MÁRAI - Janiec-Nyitrai, Agnieszka (Porównania, 2012)
The article is dedicated to the philosophy of travelling and discovering spaces depicted in the travelling literature of Karl Čapek (Letters from a journey) and Sándor Márai (While travelling). The key aspects in the texts include the rebellion against the mass experience, searching for a new perspective, protest against a careless outlook, but also, an unwillingness to trivialise the cognitive process, which should be understood as an active and creative attitude towards the reality which one gets to know, vividly visible in the texts of both authors.